Utility of Rapid Nasopharyngeal Swab for Respiratory Pathogens in the Diagnosis of Viral Infections in Children Hospitalized with Fever: A Prospective Validation Study to Improve Antibiotic Use - Danilo Buonsenso; Rosa Morello; Francesco Mariani; Bianca Mazzoli; Cristina De Rose; Ilaria Lazzareschi; Francesca Raffaelli; Rita Blandino; Maurizio Sanguinetti; Piero Valentini (MDPI AG, 2024)
Introduction: Fever is among the most common reason for medical assessment and antibiotic prescription in practice. The aim of this study was to evaluate positive and negative predictive values of rapid nasopharyngeal swabs for respiratory pathogens to discriminate viral from bacterial infections. Methods: We prospectively tested children with signs and/or symptoms of infections (e.g., fever, cough, wheezing, suspected urinary tract infection) admitted to a paediatric department. Following discharge, clinical phenotypes were assigned defining a cohort of children having probable/certain viral infection, probable/certain bacterial infection, other inflammatory conditions or healthy controls. Results: In this study, 190 children were enrolled (50.5% females, median age 30.5 (8-86) months). In total, 102 patients (53.7%) were affected by respiratory viral infections, 16 (8.4%) by bacterial infections, 29 (15.3%) were healthy controls and 43 (22.6%) were affected by another pathological condition manifested with fever. In total, 84.3% of patients classified as viral infection tested positive for viruses, compared with 18.8% of patients with bacterial infection (p < 0.001), 18.6% of patients with other condition (p < 0.001) and 17.2% of control patients (p < 0.001). The positive predictive value of NPSs in the diagnosis of viral infection was 88.6% and the negative predictive value was 75.0%. Conclusion: Our findings suggest that rapid NPS tests for respiratory viruses are a useful tool to confirm viral infections in children with fever and improve antibiotic use.